Healthcare managers’ involvement in change: bridging the gap between senior leadership, managers and frontline staff - Callum M Brown (British Journal of Healthcare Management, 2026)
In today's rapidly evolving health and care landscape, it is almost certain that healthcare managers will be asked to lead, or at least be involved in, making a change at some point in their career. Business change manager Callum M Brown explains why there is often a mismatch between frontline staff and managers’ perspectives on change, and ways that managers can reduce change resistance in their teams.